The Ion Composition of Saturn's Equatorial Ionosphere as Observed by Cassini. Issue 12 (19th June 2019) - Cravens, T. E.; Moore, L.; Waite, J. H.; Perryman, R.; Perry, M.; Wahlund, J.‐E.; Persoon, A.; Kurth, W. S.
Abstract: The Cassini Orbiter made the first in situ measurements of the upper atmosphere and ionosphere of Saturn in 2017. The Ion and Neutral Mass Spectrometer (INMS) found molecular hydrogen and helium as well as minor species including water, methane, ammonia, and organics. INMS ion mode measurements of light ion species (H +, H2 +, H3 +, and He + ) and Radio and Plasma Wave Science instrument measurements of electron densities are presented. A photochemical analysis of the INMS and Radio and Plasma Wave Science data indicates that the major ion species near the ionospheric peak must be heavy and molecular with a short chemical lifetime. A quantitative explanation of measured H + and H3 + densities requires that they chemically react with one or more heavy neutral molecular species that have mixing ratios of about 100 ppm. Plain Language Summary: Solar ultraviolet radiation is absorbed by Saturn's upper atmosphere and produces electrically charged molecules (or ions) and electrons in a region called the ionosphere. The Ion and Neutral Mass Spectrometer (INMS) instrument onboard the Cassini Orbiter made the first direct measurements of the composition of Saturn's ionosphere when the Cassini spacecraft flew through the upper atmosphere in the equatorial region. This paper reports on INMS measurements of the abundances of ionospheric protons, charged molecular hydrogen and helium, and protonated molecular hydrogen as functions of altitude and latitude. The paper also describes a photochemical analysis of the data indicating the presence in the upper atmosphere of heavy molecular species such as water, methane, and ammonia, thought to come from the rings. The deduced mixing ratio of these species relative to hydrogen is about a part in 10, 000, which is consistent with measurements made using the neutral mode of the INMS. The simple chemical analysis was also able to reproduce the densities of electrons measured by the Radio and Plasma Wave Science instrument onboard Cassini. This paper contributes to our growing appreciation of the strong effect that the rings have on Saturn's atmosphere. Key Points: A heavy molecular species in Saturn's atmosphere is needed to explain the measured ion composition Measured ion and electron densities in the main Saturn ionosphere can be explained by solar ionizing radiation Both neutral and plasma measurements made at Saturn by Cassini suggest a strong ring‐atmosphere interaction